2006
DOI: 10.1002/cncr.22139
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of extracapsular extension of pelvic lymph node metastasis in patients with bladder cancer treated in the contemporary era

Abstract: Disease overview: Cutaneous T‐cell lymphomas are a heterogenous group of T‐cell lymphoproliferative disorders involving the skin, the majority of which may be classified as Mycosis fungoides (MF) or Sézary syndrome (SS). Diagnosis: The diagnosis of MF or SS requires the integration of clinical and histopathologic data. Risk‐adapted therapy: Tumor, node, metastasis, and blood (TNMB) staging remains the most important prognostic factor in MF/SS and forms the basis for a “risk‐adapted,” multidisciplinary approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 232 publications
(277 reference statements)
1
10
2
1
Order By: Relevance
“…Higher TNM N category, which is related to both the number of positive nodes and the size of metastases, has been associated with worse outcome in some studies, though not uniformly [33,34]. Additionally, the presence or absence of an intact lymph node capsule has been correlated with prognosis; patients with capsular perforation have diminished survival compared to those without [20,33], although this result has not been corroborated by others [35]. Finally, having a larger proportion of nodes positive for metastatic disease is also associated with diminished prognosis.…”
Section: Lymph Node Status and Prognosismentioning
confidence: 91%
See 1 more Smart Citation
“…Higher TNM N category, which is related to both the number of positive nodes and the size of metastases, has been associated with worse outcome in some studies, though not uniformly [33,34]. Additionally, the presence or absence of an intact lymph node capsule has been correlated with prognosis; patients with capsular perforation have diminished survival compared to those without [20,33], although this result has not been corroborated by others [35]. Finally, having a larger proportion of nodes positive for metastatic disease is also associated with diminished prognosis.…”
Section: Lymph Node Status and Prognosismentioning
confidence: 91%
“…The ratio of the number of positive nodes to the overall number of identified nodes has been termed lymph node density, or lymph node ratio. It has been reported that patients with lymph node densities over 20-25% experience diminished survival [24,31,[35][36][37].…”
Section: Lymph Node Status and Prognosismentioning
confidence: 99%
“…Eine der bis heute wohl wichtigsten prognostischen Parameter stellt das extrakapsuläre Wachstum dar, welches im Rahmen einer multivariaten Analyse den stärksten prädikti-ven Wert ausmachte [8]. Hingegen konnten Kassouf et al [14] diese Beobachtung im Rahmen ihrer Studie nicht bestäti-gen. Diese Studie basiert aber nur auf den den Autoren vorliegenden Pathologieberichten, eine neuerliche Aufarbeitung der Schnittpräparate erfolgte nicht. Es wird weiter angenommen, dass bei Nachweis von tumorpositiven LK mit extrakapsulä-rem Wachstum ein aggressiverer Tumortyp mit einer höheren Wahrscheinlichkeit und Geschwindigkeit der Metastasierung vorliegt.…”
Section: Lymphknoten-density Und Lymphknoten Mit Extrakapsulärem Wachunclassified
“…Multivariate analyses confirmed that extracapsular extension of LN metastases was the strongest negative predictor for RFS [19]. However, others did not find a significant association between extracapsular extension and survival after RC, leading to issue of whether this pathological finding is really of importance [55]. …”
Section: Extracapsular Extension Of Lymph Node Metastasismentioning
confidence: 99%
“…Ghoneim and Abol-Enein introduced the concept of sentinel region (intrapelvic LNs) rather than sentinel node [6, 7]. Involvement of the intrapelvic LNs may be the first step in nodal metastasis in most BCs and skip lesions might be very rare [26, 47, 52, 5557]. However, higher number of patients and longer followup is needed before widespread practice is accepted.…”
Section: The Concept Of “Sentinel Lymph Node”mentioning
confidence: 99%